STRATEGY DEVELOPMENT AND IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE (GCG) ON BUMN AND BUMD IN INDONESIA - Nuryan, Iwan (AdBispreneur, 2016)
ABSTRACTGood Corporate Governance (GCG) is a important measure in the corporation an business practice. Some fact that showed lowed rank in the implementation of GCG in Indonesia, had been one of important factors that caused economic crisis and slow face of economic growth in Indonesia, This is had been a trigger to all stakeholders to continue encourage implementation of GCG in Indonesia. There are four important principal in GCG that now continue to encourage, fairness, transparency, accountability, and responsibility.At the level of practice, the application of GCG in Indonesia, especially in BUMN and BUMD is still very low. Some of the obstacles that hinder the implementation of GCG in Indonesia, especially in BUMN and BUMD are the internal constraints, external constraints, and constraints of ownership. To overcome the obstacles it needs to be stressed to continue to raise awareness of all stakeholders about the important of GCG implementation, strengthening the legal basis of GCG implementation, strengthening  government system reform until clean government that free from corruption had been establish, and do some reform throughout the business corporation that runs in Indonesia. Keywords : strategy, GCG, BUMN, BUMD   STRATEGI PENGEMBANGAN DAN PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) BAGI BUMN DAN BUMD DI INDONESIA ABSTRAKGood Corporate Governance (GCG) merupakan sebuah instrumen penting dalam praktek bisnis dan perusahaan. Fakta menunjukkan bahwa rendahnya penerapan GCG di Indonesia telah menjadi salah satu faktor penting terjadinya krisis ekonomi di Indonesia serta lambatnya pertumbuhan ekonomi di Indonesia. Hal ini telah menjadi pendorong berbagai pihak untuk terus mendorong penerapan GCG di Indonesia. Empat prinsip penting dalam GCG yang saat ini terus didorong untuk diterapkan adalah kewajaran, transparansi, akuntabilitas, dan responsibilitas. Pada tataran praktek, penerapan GCG di Indonesia, khususnya pada BUMN dan BUMD masih sangat rendah. Beberapa kendala yang menghambat penerapan GCG di Indonesia, khususnya pada BUMN dan BUMD adalah kendala internal, kendala eksternal, dan kendala kepemilikan. Untuk mengatasi berbagai kendala tersebut maka perlu ditekankan untuk terus meningkatkan kesadaran berbagai pihak akan pentingnya penerapan GCG,   memperkuat   dasar  hukum  penerapan  GCG,   mereformasi  sistem  pemerintahan  hingga terciptanya praktek clean government yang bebas KKN serta reformasi di seluruh korporasi bisnis yang berjalan di Indonesia. Kata kunci : strategy, GCG, BUMN, BUMD